Highly efficient planar perovskite solar cells through band alignment engineering. Issue 10 (4th September 2015) - Correa Baena, Juan Pablo; Steier, Ludmilla; Tress, Wolfgang; Saliba, Michael; Neutzner, Stefanie; Matsui, Taisuke; Giordano, Fabrizio; Jacobsson, T. Jesper; Srimath Kandada, Ajay Ram; Zakeeruddin, Shaik M.; Petrozza, Annamaria; Abate, Antonio; et al.
Abstract : Planar perovskite solar cells exhibit a conduction band misalignment of the perovskite with TiO2, but not with SnO2 . The system using the latter yielded power conversion efficiencies over 18%. Abstract : The simplification of perovskite solar cells (PSCs), by replacing the mesoporous electron selective layer (ESL) with a planar one, is advantageous for large-scale manufacturing. PSCs with a planar TiO2 ESL have been demonstrated, but these exhibit unstabilized power conversion efficiencies (PCEs). Herein we show that planar PSCs using TiO2 are inherently limited due to conduction band misalignment and demonstrate, with a variety of characterization techniques, for the first time that SnO2 achieves a barrier-free energetic configuration, obtaining almost hysteresis-free PCEs of over 18% with record high voltages of up to 1.19 V.